2006
DOI: 10.1080/09563070701776570
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prone ventilation on intra-abdominal pressure

Abstract: Objective. Raised intra-abdominal pressure (IAP) has a number of significant adverse physiological effects and it is therefore important to know whether prone ventilation increases IAP. The aim of this study was to address this question. Design. An observational study was carried out to examine the effect of prone ventilation on IAP using a consecutive sample of 10 patients with acute respiratory distress syndrome undergoing mechanical ventilation in the prone position. Measurement of IAP supine (baseline) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Two studies unloaded the abdomen [36,37] while five did not [38-42], and one study did not report on abdominal unloading [43]. Finally, one study randomized abdominal suspension [44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies unloaded the abdomen [36,37] while five did not [38-42], and one study did not report on abdominal unloading [43]. Finally, one study randomized abdominal suspension [44].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies measured IAP during PV in critically ill patients, and another study concerned obese patients during elective surgery (Table 2 ). Two studies unloaded the abdomen [ 36 , 37 ] while five did not [ 38 - 42 ], and one study did not report on abdominal unloading [ 43 ]. Finally, one study randomized abdominal suspension [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prone position modifies this situation, and some authors have reported decreased intra-abdominal pressure; (34) in the end, the abdominal wall becomes more rigid, with a resulting increase in intra-abdominal pressure. (35-37) …”
Section: Methodsmentioning
confidence: 99%
“…In patients demonstrating no abdominal disease, a minimal, though substantial increase of intra-abdominal pressure without intra-abdominal compartment syndrome occurred as a result of prone positioning during a period of up to 2 h [ 99 , 134 , 135 ] (evidence level 2b). Likewise, no impact on splanchnic perfusion was demonstrated [ 157 , 187 ].…”
Section: Prone Position In Patients With Acute Pulmonary Disordersmentioning
confidence: 99%